Morphological Changes, Cadherin Switching, and Growth Suppression in Pancreatic Cancer by GALNT6 Knockdown - Yunus Emre Tarhan; Taigo Kato; Miran Jang; Yoshimi Haga; Koji Ueda; Yusuke Nakamura; Jae-Hyun Park (Neoplasia: An International Journal for Oncology Research, 2016)
Pancreatic cancer reveals the worst prognosis among human cancers with little improvement in its clinical outcome in the last three decades. We previously suggested that polypeptide N-acetylgalactosaminyltransferase 6 (GALNT6), which catalyzes O-type glycosylation of Mucin 1, might be a promising molecular target for drug development for breast cancer. In this study, we report upregulation of GALNT6 in pancreatic cancer cells where Mucin proteins are highly O-glycosylated. We found that knockdown of GALNT6 with small interfering RNA in pancreatic cancer cells decreased the amount of Mucin 4 protein as well as that of its transcript, reduced the levels of human epidermal growth factor receptor 2 and extracellular signal–regulated kinase, and significantly reduced pancreatic cancer cell viability. Interestingly, knockdown of GALNT6 caused drastic morphological changes of pancreatic cells, accompanied with the cadherin switching from P-cadherin to E-cadherin. Considering important roles of Mucin 4 in growth and invasion, our findings imply that targeting GALNT6 is a very promising therapeutic strategy for treatment of pancreatic cancer patients who still have very limited treatment modalities.